2021
DOI: 10.1038/s41598-021-84713-9
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic acid and nitrogen efficiently protect early seedlings growth stage from salt stress damage in Sorghum

Abstract: Salinity one of environmental factor that limits the growth and productivity of crops. This research was done to investigate whether GA3 (0, 144.3, 288.7 and 577.5 μM) and nitrogen fertilizer (0, 90 and 135 kg N ha−1) could mitigate the negative impacts of NaCl (0, 100, and 200 mM NaCl) on emergence percentage, seedling growth and some biochemical parameters. The results showed that high salinity level decreased emergence percentage, seedling growth, relative water content, chlorophyll content (SPAD reading), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
9
27
0
3
Order By: Relevance
“…Salt stress reduces the contents of Chl a, Chl b, Chl a + b, and Car which causes a reduction in photosynthesis. In line with our results are other findings that salt stress reduces the chlorophyll content and inhibits chlorophyll biosynthesis in sorghum [55,56]. This happens by the inactivation of enzymes involved in the synthesis of photosynthetic pigments [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Salt stress reduces the contents of Chl a, Chl b, Chl a + b, and Car which causes a reduction in photosynthesis. In line with our results are other findings that salt stress reduces the chlorophyll content and inhibits chlorophyll biosynthesis in sorghum [55,56]. This happens by the inactivation of enzymes involved in the synthesis of photosynthetic pigments [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…In our vision, sea fennel has the potential for more extensive cultivation and for the ready-to-eat market as a baby-leaf vegetable, due not only to its organoleptic characteristics but also to its richness in terms of health-promoting compounds and its suitability for cultivation in saline conditions, an important aspect for the Mediterranean environment. This aspect would be crucial since soil salinity is currently the most important environmental stress limiting crop production in arid and semi-arid areas [20], and, in the near future this trend is expected to worsen [21]. For this purpose, we evaluated the effect of the salinity level of the nutrient solution in a floating system on the growth, quality, and shelf-life of C. maritimum during a storage period.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellic acid is an important hormone in defending the plant against stress conditions (Alharby et al, 2021). Studies have shown that externally applied gibberellic acid can increase seed germination and salt tolerance of seeds (Chauhan et al, 2019;Oral et al, 2019;Ali et al, 2021). In this study, it was determined that the negative effect of salinity could be reduced by gibberellic acid pre-treatment.…”
Section: Discussionmentioning
confidence: 93%